2002
DOI: 10.1098/rspb.2002.1984
|View full text |Cite
|
Sign up to set email alerts
|

Partnership status and the temporal context of relationships influence human female preferences for sexual dimorphism in male face shape

Abstract: Secondary sexual characteristics may indicate quality of the immune system and therefore a preference for masculinity may confer genetic benefits to offspring; however, high masculinity may be associated with costs of decreased paternal investment. The current study examined women's preferences for masculinity in male faces by using computer graphics to allow transformation between feminine and masculine versions of individual male faces. We found that preferences for masculinity are increased when women eithe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
340
10
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 378 publications
(378 citation statements)
references
References 30 publications
27
340
10
1
Order By: Relevance
“…However, this is not the case, since only one's opposite-sex parental prototype influences one's mate choice. This is in line with the results of observations and experiments among animals and humans ( Vos 1995;Little et al 2002b;Bereczkei et al 2004). A study using molecular techniques has shown significantly higher HLA allele matches between the donors of a woman's most preferred donor and a woman's father than between the preferred donors and her mother ( Jacob et al 2002).…”
Section: R E T R a C T E Dsupporting
confidence: 77%
See 2 more Smart Citations
“…However, this is not the case, since only one's opposite-sex parental prototype influences one's mate choice. This is in line with the results of observations and experiments among animals and humans ( Vos 1995;Little et al 2002b;Bereczkei et al 2004). A study using molecular techniques has shown significantly higher HLA allele matches between the donors of a woman's most preferred donor and a woman's father than between the preferred donors and her mother ( Jacob et al 2002).…”
Section: R E T R a C T E Dsupporting
confidence: 77%
“…These findings appear to support the sexual imprinting hypothesis and provide additional evidence for the results that have been found in former studies (Bereczkei et al 2002(Bereczkei et al , 2004Little et al 2002b). Young adults show facial similarity to their partner's opposite parent that may come from a socialization process: children learn the particular features of the opposite-sex phenotype during childhood, and later they prefer long-term mates who show a certain degree of similarity to this parent.…”
Section: R E T R a C T E Dsupporting
confidence: 74%
See 1 more Smart Citation
“…(1 = very unlikely, 7 = very likely). The two contexts were used because they can shift responses in subtle but statistically detectable manner (Little, Jones, Penton-Voak, Burt, & Perrett, 2002;Roberts, Little et al, 2005) and give some insight into the selection pressure underlying the preference: those expressed more strongly in the long-term context indicate relatively higher attention to cues of paternal investment, while preferences more strongly expressed in the general attractiveness context may emphasize cues of good genes (Gangestad & Simpson, 2000).…”
Section: Materials and Proceduresmentioning
confidence: 99%
“…-scrolling to one side of the face would not always make the face appear taller). Such interactive tests have been successfully used in previous face research (Little, Jones, Penton-Voak, Burt, & Perrett, 2002;Perrett et al, 1998).…”
Section: Methodsmentioning
confidence: 99%